Mathematical creative problem solving ability and self-efficacy: (a survey with eight grade students). Issue 3 (February 2019) - Yuliani, A; Kusumah, Y S; Sumarmo, U
Abstract: This study is a survey that aims to analyze students' creative problem solving ability, self-efficacy, and associations. This survey involved 25 eighth grade, a test of mathematical creative problem solving ability (MCPSA), and a mathematical self-efficacy (MSE) scale. The MCPSA essay test contains 3 items and the MSE scale is compiled in Likert's model. The survey found that students MCPSA were at low grade level and students were aware of the difficulties in some items of MCPSA tasks. Even tough on MSE, the survey found that students were at fairly good level. The other findings, there is no association between MCPSA and MSE.